Metastatic disease in uveal melanoma: importance of a genetic profile?. Issue 5 (October 2015) - Van Beek, Jackelien G.M.; Koopmans, Anna E.; Vaarwater, Jolanda; Verdijk, Rob M.; de Klein, Annelies; Naus, Nicole C.; Kiliç, Emine
Abstract : Mutation of SF3B1 has been identified in low-grade uveal melanoma with a good prognosis. In this study, we compare chromosomal aberrations and gene mutations between a primary uveal melanoma and its multiple hepatic and peripancreatic metastases. DNA was isolated from a large primary uveal melanoma after fractionated stereotactic radiotherapy and three distinct metastases (two liver samples and one peripancreatic lymph node) to perform single-nucleotide polymorphism array and fluorescent in-situ hybridization. We analyzed mutations in uveal melanoma target genes BAP1, GNAQ, GNA11, SF3B1, and EIF1AX. The primary tumor showed no abnormalities in chromosome 3, whereas metastases showed deletion of at least 3q12.1-q24 and the BAP1 gene was not mutated. All samples indicated the following consistent chromosomal aberrations: loss of 1p, gain of 6p, and gain of 8q. Subsequently, heterozygous SF3B1 and heterozygous GNA11 mutations were observed. The metastases showed more genetic aberrations than the primary tumor and may therefore represent the genetic status of the tumor before irradiation, whereas the current primary tumor shows presumably irradiation artifacts. An early occurring mutation in GNA11 was observed in all samples. The SF3B1 mutation seems to predispose for late metastatic disease in the absence of a BAP1 mutation.